Mental Fatigue Alters Cortical Activation and Psychological Responses, Impairing Performance in a Distance-Based Cycling Trial - Pires, Flávio O.; Silva-Júnior, Fernando L.; Brietzke, Cayque; Franco-Alvarenga, Paulo E.; Pinheiro, Fabiano A.; de França, Nanci M.; Teixeira, Silmar; Meireles Santos, Tony (Frontiers in Physiology, 2018)
Purpose: We sought to verify if alterations in prefrontal cortex (PFC) activation and psychological responses would play along with impairments in pacing and performance of mentally fatigued cyclists. Material and Methods: Eight recreational cyclists performed two preliminary sessions to familiarize them with the rapid visual information processing (RVP) test, psychological scales and 20 km cycling time trial (TT20km) (session 1), as well as to perform a VO2MAX test (session 2). Thereafter, they performed a TT20km either after a RVP test (30 min) or a time-matched rest control session (session 3 and 4 in counterbalanced order). Performance and psychological responses were obtained throughout the TT20km while PFC electroencephalography (EEG) was obtained at 10 and 20 km of the TT20km and throughout the RVP test. Increases in EEG theta band power indicated a mental fatigue condition. Repeated-measures mixed models design and post-hoc effect size (ES) were used in comparisons. Results: Cyclists completed the trial 2.7 % slower in mental fatigue (34.3 ± 1.3 min) than in control (33.4 ± 1.1 min; p = 0.02; very large ES), with a lower WMEAN (224.5 ± 17.9 W vs 240.2 ± 20.9 W, respectively; p = 0.03; extremely large ES). There was a higher EEG theta band power during RVP test (p = 0.03; extremely large ES), which remained during the TT20km (p = 0.01; extremely large ES). RPE increased steeper in mental fatigue than in control, together with isolated reductions in motivation at 2th km (p = 0.04; extremely large ES), felt arousal at the 2nd and 4th km (p = 0.01; extremely large ES), and associative thoughts to exercise at the 6th and 16th km (p = 0.02; extremely large ES) of the TT20km. Conclusions: Mentally fatigued recreational cyclists showed impaired performance, altered PFC activation and faster increase in RPE during a TT20km.